2021
DOI: 10.1007/s10668-021-01490-1
|View full text |Cite
|
Sign up to set email alerts
|

SWOT analysis of renewable energy sector in Mazowieckie Voivodeship (Poland): current progress, prospects and policy implications

Abstract: Renewable energy (RE) plays an increasingly important role in the economy of almost every country in the world. In order to examine the state of renewable energy (RE) in Mazowieckie Voivodeship (Poland), a literature review was carried out, anonymous surveys were conducted, a SWOT (Strenghts, Weaknesses, Opportunities, Threats) and TOWS analysis were carried out and the potential of RE in Mazowieckie voivodship was estimated. The total capacity of all installations is equal to 712 MW. In recent months, number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…SWOT analysis is a straightforward, popular and well-known technique, that implies that an organization's resources (which constitute its strengths and weaknesses) should match the demands and pressures from its external environment (manifested as a set of opportunities and threats) as effectively as possible and, with change, stay matched in dynamic and turbulent times [42]. Several authors have used this approach for similar studies [43,44] to evaluate the current situation and future prospects by simultaneously considering internal and external factors [45].…”
Section: Discussionmentioning
confidence: 99%
“…SWOT analysis is a straightforward, popular and well-known technique, that implies that an organization's resources (which constitute its strengths and weaknesses) should match the demands and pressures from its external environment (manifested as a set of opportunities and threats) as effectively as possible and, with change, stay matched in dynamic and turbulent times [42]. Several authors have used this approach for similar studies [43,44] to evaluate the current situation and future prospects by simultaneously considering internal and external factors [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a system, uncertainty grows proportionally with complexity, and in the case of the CE concept, with addition to the intrinsic factors related to the functioning of the system, there are dominant uncertainties related to community behaviour, attitudes and practices which can best be described using SWOT analysis. The SWOT analysis applied to the CE concept should fundamentally focus on innovative social transformation (social innovation) as an essential factor that ensures the successful implementation of CE in developing countries [31].…”
Section: B Swot Analysis For Social Impactmentioning
confidence: 99%
“…The results showed that digital energy transformation is an effective approach to optimize energy allocation and improve energy planning. Igli nski et al 47 developed renewable energy in Poland. In this study, SWOT analysis was used to identify strategies.…”
Section: Swot Analysis In Renewable Energy Strategy Developmentmentioning
confidence: 99%